Legality, Packaging, and Taste on Traditional Product Purchasing DecisionsLegality, Packaging, and Taste on Traditional Product Purchasing Decisions - Talita Fidela Vania Azarin; Basthoumi Muslih (Journal of International Conference Proceedings, 2025)
The growth of the traditional food MSME sector increasingly shows an important contribution to the regional economy, but increasing competition requires business actors to strengthen legality, improve packaging design, and maintain taste that influences purchasing decisions as a factor. This work seeks to examine the impact of legality, packaging, and taste on purchasing decisions for Opak Gambir Matari Zakaya products. The study uses a causal associative quantitative approach, involving 80 respondents through purposive sampling. A questionnaire with a Likert scale is used as a measuring tool for data collection, tested using validity and reliability tests, and analyzed through multiple linear regression. Simultaneously, all three predictors exert a notable effect on buyer choices which are the results of this study. Partially, packaging is the single most influential factor, while legality and taste do not show any influence. This finding indicates that consumers are more responsive to the visual appeal of packaging in the initial purchasing process. This study suggests that MSME actors strengthen packaging innovation while maintaining legal eligibility and taste quality to increase product trust and competitiveness.